Penggunaan Aplikasi Office untuk Meningkatkan Pengetahuan Administrasi pada Fasilitator Taman Belajar di Karanganyar - Norhikmah, Norhikmah; Rumini, Rumini; Pratama, Rifqy Rayhan Andi Riga; Kusuma, Prita Widia (Madani : Indonesian Journal of Civil Society, 2025)
Mastery of office applications is an important skill for learning park facilitators and managing administration effectively. This community service activity aims to improve the knowledge and administrative skills of learning park facilitators in Karanganyar through training in Office applications, such as Microsoft Word, Excel, and PowerPoin. Learning Park is one of the non-formal educational facilities for early childhood and school-age children under the auspices of the Yayasan Rumah Sekolah Indonesia. This educational facility can function as a supplement to or replacement for the widely available formal education. The early childhood education institution, Learning Park, falls into the category of community-based self-help initiatives, which has been operating for about one year and has five facilitators, with the number of students increasing each academic year. Therefore, teachers must enhance the facilitators' knowledge, including administration, financial reporting, and creating engaging teaching processes. The steps of implementing this service training are: first, developing training materials and test questions; second, conducting a pre-test and the training itself; and finally, concluding with an evaluation process through a questionnaire. The results of the service training on office application usage showed an improvement in facilitators' knowledge, with an average score increase of 22% from the pre-test results.